Learning L3 English Early: A Danger to L1 Indonesian Language Acquisition? - Irnanda, Septhia; Sarair, Sarair (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Since the future of the world is English, many countries now include English in their primary education curriculum, so language proficiency can be achieved more quickly and effectively. As two or more languages knowledge are competing linguistically in the brain, the early introduction to English means putting the other languages known by the Indonesian English language learners in a competition. On the other hand, despite its controversy, bilingualism and multilingualism, when achieved fully and proportionally, is cognitively and socially beneficial. This article reviews the potential effects of including English early in the Indonesian curriculum and the recommendation for the Indonesian’s future multilingual education and research. The discussion resulted in some important conclusions. Firstly, considering the Indonesian-English far typological distance, learning English requires some time and cognitive effort. For Indonesian bilinguals/multilingual, this means early introduction to English means higher confidence in producing the language verbally later on. During this early learning of English, the Indonesian language (and any other ethnic language that forms the speaker’s identity should also be used simultaneously to create the same purpose; a sense of belonging towards and confidence in using the language(s). In short, multilingualism that includes foreign language instruction; national and minority language use and maintainance, should be enhanced and normalised from childhood.